Suppressor of fused-restrained Hedgehog signaling in chondrocytes is critical for epiphyseal growth plate maintenance and limb elongation in juvenile mice - Xiu, Chunmei; Gong, Tingting; Luo, Na; Ma, Linghui; Zhang, Lei; Chen, Jianquan (Frontiers in Cell and Developmental Biology, 2022)
Hedgehog (Hh) signaling plays multiple critical roles in regulating chondrocyte proliferation and differentiation during epiphyseal cartilage development. However, it is still unclear whether Hh signaling in chondrocytes is required for growth plate maintenance during juvenile growth, and whether sustained activation of Hh signaling in chondrocytes promotes limb elongation. In this study, we first utilized Hh reporter mice to reveal that Hh signaling was activated in resting and columnar chondrocytes in growth plates of juvenile and adult mice. Next, we genetically modulated Hh signaling by conditionally deleting Smo or Sufu in all or a subpopulation of growth plate chondrocytes, and found that ablation of either Smo or Sufu in chondrocytes of juvenile mice caused premature closure of growth plates and shorter limbs, whereas Osx-Cre-mediated deletion of either of these two genes in hypertrophic chondrocytes did not lead to obvious growth plate defects, indicating that Hh signaling mainly functions in immature chondrocytes to maintain growth plates at the juvenile stage. At the cellular level, we found that chondrocyte-specific ablation of Smo or Sufu accelerated or suppressed chondrocyte hypertrophy, respectively, whereas both decreased chondrocyte proliferation and survival. Thus, our study provided the first genetic evidence to establish the essential cell-autonomous roles for tightly-regulated Hh signaling in epiphyseal growth plate maintenance and limb elongation during juvenile growth.